Conceptualising Islamic human resource management principles in the context of Palestine - Md Faruk, Abdullah; Bahyah, Abdul Halim; Shaban Jamal, Ayyat (Penerbit Universiti Sultan Zainal Abidin, 2020)
The purpose of this study is to conceptualise Islamic Human Resource Management (HRM) principles in the context of Palestine by investigating the current and standard practices of Islamic HRM principles in the West Bank in Palestine. The primary focus is more on the implementation and awareness about Islamic HRM principles in the large institutions and organisations including governmental and non-governmental bodies like banks, universities, ministries and other key organisations. The paper takes the form of a library research approach based on an extensive review of relevant literature. It examines available research works done in the field of HRM and Islamic Human resources in the West Bank in Palestine. It aims to summarise the current trends and possible future implications of the present behaviours and practices in the Palestinian organisations and their awareness about the importance of Islamic HRM. The conceptualisation of Islamic principles and their application to HRM is based upon several previous studies. The concept of Islamic HRM is developed from the primary sources of the Shariah, i.e. Quran and Sunnah. The reviewed literature reveals a considerable misunderstanding of the critical concepts of the Islamic HRM and a lack of awareness about their implications to the organisations. Although most organisations claim that their practices are in line with the principles of Islam and they care a lot about fair treatment and honesty, nevertheless the reality is that there is a marginal implementation of these principles. Furthermore, the Israeli occupation has created many limitations on Palestinian organisations. The limitations that this study faced are the lack of data from primary resources and official data. Furthermore, there is a lack of research papers on Islamic HRM in the Palestinian context because of the limited resources and empirical studies in this area. The study is significant for decision-makers and policymakers in Palestine and shows them the importance of implementing Islamic HRM for their organisations.